(untitled) (Journal of Medical & Health Sciences Review, 2025)
Breast cancer is recognized as a global issue affecting millions of women with a greater impact on their lives. Worldwide, breast cancer is among the most prevalent forms of the disease. Throughout their lives, 12% of American women will experience a breast cancer diagnosis, and in 2017, more than 250,000 new cases were reported to the medical community. This study was conducted in a cross-sectional approach retrospectively in a tertiary care hospital in Karachi, Pakistan, in which data of all types of cancer patients were gathered from 1st January 2023 – 31st December 2023 in a pre-designed/translated data collection form. Initial analysis was piloted in the form of descriptive statistics such as percentages and frequencies. Chi-square tests and Monte Carlo tests were used to analyze breast cancer occurrence and risk factor associations, considering p-value <0.05 as statistically significant. Following the analysis, an incidence of 11.51 and a prevalence of 13.36 were calculated for 2023. confirms the occurrence of breast cancer among middle-aged women (Mean age 48.67±12.14 years) at an advanced stage in Karachi, Pakistan. A highly statistically significant correlation was detected between hormonal status and stage (p < 0.01), type of breast cancer and stage (p < 0.01), gender and habits (p < 0.01), and ethnicity and habits (p < 0.01), respectively. On the other hand, marital status was not correlated to the stage of breast cancer (p = 0.913). No significant association was found between ethnicity and segregated hormone receptor status. These findings suggest the need for interventions such as awareness programs, lifestyle adoption, and breastfeeding /hormonal usage training programs to prevent diagnosis postponements, awareness, and prevention, thus reducing disease load. Also, the unavailability of data highlights the need for a centralized national cancer control body promoting the entry of updated data of these patients across the private and public sectors.